1990
DOI: 10.1128/jvi.64.9.4108-4114.1990
|View full text |Cite
|
Sign up to set email alerts
|

Bovine coronavirus mRNA replication continues throughout persistent infection in cell culture

Abstract: The existence of viral mRNA replicons was demonstrated in cells infected with the bovine coronavirus by showing a minus-strand counterpart and a corresponding replicative intermediate for each subgenomic mRNA species. mRNA replication is thus a universal property of coronaviruses, since this is now the third coronavirus for which it has been demonstrated. During the acute phase of infection (first 48 h), minus and plus strands accumulated at the same rate initially, but maximal accumulation of minus strands pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(152 citation statements)
references
References 22 publications
8
144
0
Order By: Relevance
“…The virus titers varied within a constant range (Fig. 2) but no cycling as described, for instance, for bovine coronavirus (Hofmann et al, 1990) was observed.…”
Section: Discussionmentioning
confidence: 75%
“…The virus titers varied within a constant range (Fig. 2) but no cycling as described, for instance, for bovine coronavirus (Hofmann et al, 1990) was observed.…”
Section: Discussionmentioning
confidence: 75%
“…Packaging of subgenomic RNAs has been reported for TGEV (Sethna et al, 1991), BCoV (Hofmann et al, 1990), and IBV (Zhao et al, 1993) but not for MHV, suggesting that their incorporation is not mediated by N protein-leader interaction. Whereas for TGEV and IBV the relative packaging of subgenomic RNAs was found to be inefficient, genomic RNA appearing in virions at a more than 10-fold molar excess over any subgenomic RNA species, the BCoV subgenomic N and M mRNAs appeared to be packaged as abundantly as the genome (Hofmann et al, 1990). A reevaluation for TGEV revealed that the detection of subgenomic RNAs in virions was related to the purity of virus preparations, indicating that mRNAs were not specifically encapsidated (Escors et al, 2003).…”
Section: N-rna Interactionsmentioning
confidence: 98%
“…In general, DI RNAs contain the entire 5 0 -and 3 0 -untranslated genome regions and, in most cases, also small parts of neighboring (or internal) coding regions (Lin and Lai, 1993). Coronavirus DI RNAs were first reported and most extensively studied for the betacoronaviruses MHV and BCoV (Chang et al, 1994;de Groot et al, 1992;Hofmann et al, 1990;Luytjes et al, 1996;Makino et al, 1984Makino et al, , 1985Makino et al, , 1988a. Subsequently, DI RNAs were also identified and characterized in alpha-and gammacoronaviruses (Izeta et al, 1999;Mendez et al, 1996;Penzes et al, 1994Penzes et al, , 1996.…”
Section: Coronavirus Cis-acting Rna Elementsmentioning
confidence: 99%